2022
DOI: 10.3390/biology11020340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Adverse Drug Reactions Associated with Filgrastim and Pegfilgrastim Using the EudraVigilance Database

Abstract: The primary prophylaxis with filgrastim (FIL) and pegfilgrastim (PEG-F) is recommended to decrease the severity of chemotherapy-induced neutropenia (CIN). The commonly reported adverse drug reactions (ADRs) with FIL and PEG-F is bone pain. ADRs pertaining to FIL and PEG-F were extracted from the European EudraVigilance (EV) database. The Individual Case Safety Reports (ICSRs) obtained from EV database that reported FIL and PEG-F as the suspected drug were analyzed. Registered ADRs (from the groups “General dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…The reason behind the distortion represented in the geographical origin of cases reported to the EV can be linked to the phenomenon that falsified medicine case reporting is more common in non-EEA countries and that there is an obligation to report all serious ADR, while in EEA countries not just the reporting but the drug supply chain regulation is tightly controlled. Although we do not know the exact explanation, what can be seen is that in the case of other research studies not related to falsified medicine ADRs, we have also found the dominance of non-EEA reports (Ferreira et al, 2022;Rastogi et al, 2022).…”
Section: Discussioncontrasting
confidence: 56%
“…The reason behind the distortion represented in the geographical origin of cases reported to the EV can be linked to the phenomenon that falsified medicine case reporting is more common in non-EEA countries and that there is an obligation to report all serious ADR, while in EEA countries not just the reporting but the drug supply chain regulation is tightly controlled. Although we do not know the exact explanation, what can be seen is that in the case of other research studies not related to falsified medicine ADRs, we have also found the dominance of non-EEA reports (Ferreira et al, 2022;Rastogi et al, 2022).…”
Section: Discussioncontrasting
confidence: 56%
“…The analysis elucidated a noteworthy discrepancy in the onset times of AEs between PEG-rhG-CSF and rhG-CSF, with a particular focus on bone pain. The These findings accentuated the necessity of diligent patient follow-up, particularly considering the possibility of patients being discharged from the hospital prior to the onset of these delayed Aes [16] . In the future, the incidence of FN holds promise for reduction through the application of advanced drug development technologies and innovations.…”
Section: Discussionmentioning
confidence: 97%
“…In this observational study, the bone pain incidence rate related to pegfilgrastim was similar to the RCT results of 27.3–38.8%. Meanwhile, when reviewing the safety data of pegfilgrastim, the overall incidence rate of ADRs was 41.3%, of which bone pain was 6.9% from the European Eudra Vigilance database [ 26 ]. There were differences in race, the range of age, and the amount of the data between two databases.…”
Section: Discussionmentioning
confidence: 99%
“…Ten AEs of leukocytosis which was included in warning and precautions in label of pegfilgrastim were reported in our study [ 27 ]. There was no unusual AE in comparison with the European Eudra Vigilance database [ 26 ].…”
Section: Discussionmentioning
confidence: 99%